2020
DOI: 10.1371/journal.pone.0243931
|View full text |Cite
|
Sign up to set email alerts
|

Physiological indices and driving performance of drivers at tunnel entrances and exits: A simulated driving study

Abstract: The entrance and exit sections of a tunnel are the accident black-spots in an expressway. For a safe operation of road tunnels, it is necessary to understand a driver’s physiological indices and driving performance when driving through tunnels. In this study, the UC-Win/Road simulation software was used to build 12 tunnel models of different lengths. A simulated driving experiment was carried out in a 6-DoF motion platform. The lateral position of vehicles characterizing the driving performance was measured us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…The mental demand also increased as the radius decreased, and the variation was much greater than that of the GRPD . This process increased the difference between the SW and OW , and the driving workload also increased [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mental demand also increased as the radius decreased, and the variation was much greater than that of the GRPD . This process increased the difference between the SW and OW , and the driving workload also increased [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, HR and RMSSD are devoted to assessing the OW of the cognitive stage. Research on driving has indicated that HR varies greatly with individuals and relates to age, gender, and health [ 57 ]. To reveal the effect on individuals, GRHR was replaced to characterize the effects of driving tasks, as illustrated in Equation (2).…”
Section: Methodsmentioning
confidence: 99%
“…Using a driving simulator, various combinations of structural parameters that are difficult to obtain on real roads were acquired to explore the impact of road design on drivers' physiological comfort. In addition, the behavioral effectiveness of driving simulators has also been verified by many researchers [30,66]. The advantage of being able to manipulate scenarios and confounding variables enabled a repetitive reproduction of conditions across participants without putting them in danger, which was an invaluable asset for addressing a wide range of questions.…”
Section: Discussionmentioning
confidence: 93%
“…Miller et al [29] used driver HR and the standard deviation of the cardiac interval to explore the relationship between driver stress and driving performance. The spatial changes in a driver's HR growth rate, root mean square of successive RR interval differences (RMSSD), pupil diameter growth rate, and vehicle lateral deviation within 300 m before and after the tunnel entrance and exit were analyzed to determine the variation rules in various tunnels [30]. Qin et al [31] discussed the impacts of color decorations on interior tunnel walls on improving the constant speed driving time and the lane offset.…”
Section: Drivers' Physiological and Behavioral Characteristics And Tunnel Safetymentioning
confidence: 99%
“…At present, scholars have carried out a lot of research on the entrance and exit sections of tunnels, which can be mainly divided into the following categories: pavement temperature fields [1][2][3], linear setting [4][5][6][7], brightness design [8][9][10][11][12][13], and operation safety [14][15][16][17][18]. Despite these studies, there are few ones on the mechanical response characteristics of the pavement structures in these sections.…”
Section: Introductionmentioning
confidence: 99%